Epidemics and pandemics : real tales of deadly diseases - Cummings, Judy Dodge (Mystery & mayhem., 2018)
Explores true stories of five of the worst epidemics and pandemics in human history--the bubonic plague, smallpox, yellow fever, Spanish influenza, and AIDS.